The Image of Women in Eastern and Western Epic literature: Shahnameh and Odyssey - Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The   research   examines two epics, one from the East and one from the West with regards to the question of woman and her images in early epic literature. The epics were selected from the literature. The epics were selected from the literature of two cultures, both of which, in different historical periods produced the most advanced civilizations of their time. The Persian epic, The Shahnameh (the book of Kings) was tooted in the ancient Indo-Iranian pagan as well as Zoroastrian traditions, an epic of approximately 60,000 couplets rewritten in the tenth century A. D. in the final, completed from which has reached us today. The Greek exemplar was the odyssey of Homer, epic with which Greek literature begins and widely influences not only the later periods of Greek literature but also the entire Western literature; this epic is also widely known in the East. Central to our study of The Shahnameh and Homeric epics were the themes of dynamism, the individuality of characters and their struggles in the epic world, the resourcefulness of the human mind ascribed to them, the subject of human crises, and irony, all of which are deep-seated components marking the central literary qualities of these epics. Women are indispensable in the early epics of both traditions and more often than not highly regarded by epic heroes in general and the narrators of the stories in particular. In both Eastern and Western example the structure split the female image in two opposite directions: one force is represented by exalted, praiseworthy, and positive images which also endow the women of The Shahnameh and the Homeric poems with powerful characteristics.